Use of neem and garlic to control rice weevil on stored rice grain / Mohammad Zulfazli Azimat - Azimat, Mohammad Zulfazli (Faculty of Plantation and Agrotechnology, 2019)
Rice (Oryza sativa) is staple food that human needs to get energy and nutrient. However, rice weevil (Sitophilus oryzae) is one of major pest that attack rice storage that cause huge economic lost in rice industry. Use of synthetic insecticide, biological control and CAM is effective but require high cost. Use of plant extraction metabolites is an alternative to control this pest because the cost is cheaper and less harmless. This research was carried out to measure the effectiveness of neem (Azadirachta indica) and garlic (Allium sativum) powder extraction toward the mortality of insect and the mortality of this insect against time. The method that used in this research is using 3 replicates that contains 100 grams of rice and the different treatment of powder which is T1 garlic powder 25 grams, T2 mixture of neem garlic powder 25 grams and T3 neem powder 25 grams and 1 control treatment each treatment. The 20 adults Sitophilus oryzae was introduced to each replicate and mortality data are taken 24 hours for 10 days consecutively. For the result, 3 treatments can cause the mortality to Sitophilus oryzae in 10 days but different level of effectiveness. The neem powder treatment is the highest effective of mortality Sitophilus oryzae followed by mixture neem garlic powder and garlic powder and no mortality on CT. It can be concluded that the plant metabolites can control the Sitophilus oryzae same as synthetic pesticide but different effectiveness.